2012
DOI: 10.1182/blood.v120.21.4042.4042
|View full text |Cite
|
Sign up to set email alerts
|

BT062, an Antibody-Drug Conjugate Directed Against CD138, Given Weekly for 3 Weeks in Each 4 Week Cycle: Safety and Further Evidence of Clinical Activity

Abstract: 4042 Background: CD138 (Syndecan-1) is highly overexpressed in various solid tumors and hematological malignancies, and represents one of the most specific target antigens for identification of multiple myeloma (MM) cells. BT062 (Biotest AG Dreieich, Germany) is an antibody-drug conjugate, comprised of the anti-CD138 chimerized MAb (nBT062) and the cytotoxic agent DM4. Once bound to CD138 on a target cell, the conjugate is internalized and releases DM4, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 3 publications
1
26
0
Order By: Relevance
“…A Chinese group reported their experience with an anti CD138 CAR on 5 refractory patients. 75 Multiple infusions were well tolerated and only mild fever was reported, stable disease was achieved in 4 out of 5 patients. Nevertheless, these are preliminary findings and…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…A Chinese group reported their experience with an anti CD138 CAR on 5 refractory patients. 75 Multiple infusions were well tolerated and only mild fever was reported, stable disease was achieved in 4 out of 5 patients. Nevertheless, these are preliminary findings and…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…Indatuximab ravtansine (BT062), an anti-CD138 monoclonal antibody conjugated with drug maytansinoid 4 (DM4), a cytotoxic maytansinoid derivative [113] has been shown to possess a favorable safety profile, with nausea, anemia, diarrhea, and fatigue as the most common adverse events in a dose-escalating phase 1 trial of 29 patients with relapsed and/or refractory MM [102]. Most patients had stable disease when treated as monotherapy [101], however when combined with lenalidomide, the ORR improved to 78% [103].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…It has been shown that maytansinoid immunoconjugates targeting CD138 exert cytotoxic activity against CD138‐positive MM cells in vitro and in mouse models (Ikeda et al , ). In a phase I/II study with immunoconjugate BT062 used as a single agent, only 1 out of 23 patients showed an objective clinical response (Heffner et al , ), however, when the same agent was combined with lenalidomide in a more recent clinical study, an overall response rate as high as 83% was observed (Kelly et al , ). While these results are indeed very promising, one should keep in mind that CD138 is another PC antigen, which is also expressed on mature epithelial cells, e.g., in the liver and skin, and that liver and skin toxicity was observed in phase I/II clinical trials, a phenomenon which could become clinically relevant with highly active CD138‐specific CAR T cells.…”
Section: Myeloma‐related Surface Molecules As Potential Targets For Cmentioning
confidence: 99%